Online dating profiles, shifting intimacies and the language of love in Papua New Guinea - Dundon, Alison ca. 20./21. Jh. (The Australian journal of anthropology, 2021)
In this paper, I explore the privileging of the language of ‘love’ on dating profiles established by Papua New Guineans active on online dating sites. In Papua New Guinea (PNG), recent accessibility to the internet has led to people going online, with the aim of attracting partners and initiating relationships based on affection. I note that companionate ideals and the vocabulary of love are central to online dating, but also reflect a wider re-imagining of intimate relationships across the country. The articulation of the vocabulary of love has a complex history in PNG, however, encompassing engagements with colonial agents, models of Christian intimacies, as well as the potent use of ‘love magic’. In this context, love can signify ambiguity or coercion as much as affection, companionship or romance. At the same time, the vocabulary of love can have a powerful and efficacious effect, generating connections and capacities, particularly associated with being ‘modern’ and Christian.